Deficient perceptions and practices concerning elevated lipoprotein(a) among specialists in Singapore - Loh, Wann Jia; Pang, Jing; Simon, Oliver; Chan, Dick C.; Watts, Gerald F. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundMultiple guidelines recommend detection of and early risk factor management for elevated lipoprotein(a) [Lp(a)]. Effective implementation requires assessment of knowledge and practices regarding elevated Lp(a) among medical specialists.AimTo assess awareness, knowledge and practices of the detection and treatment of elevated Lp(a) among specialist physicians in Singapore.MethodsSeventy-five practicing specialists in cardiology (n = 33) or endocrinology (n = 42) anonymously completed a structured questionnaire that assessed the above three aims.ResultsThe majority of respondents (83%) rated their familiarity with Lp(a) as at least average, with a greater percentage of endocrinologists being less familiar with Lp(a) than cardiologists (29% vs. 3%, P < 0.01). 57% were aware of at least one guideline or consensus statement on Lp(a), which was more frequent among cardiologists than endocrinologists (70% vs. 48%, P = 0.05). There were major gaps in knowledge of the prevalence, pathophysiological role, clinical significance and management of elevated Lp(a), correct responses being less than 30%; 44% of respondents (33% cardiologists and 52% endocrinologists) never tested for Lp(a), lack of effective treatment being the most common barrier (59%). A higher proportion of specialists that did not test for Lp(a) rated familiarity with Lp(a) as being low compared with specialists that tested for Lp(a) regularly (33% vs. 13%, P = 0.02). Education and training were considered most useful for improving care of patients with elevated Lp(a).ConclusionMajor gaps in awareness, knowledge and management of elevated Lp(a) were identified among specialists in Singapore. Education and training of specialists are required to overcome initial barriers to testing.